Quantitative Strategic Planning Matrix Analytics on Small-Scale Shoemaker Business and Finance - Wibowo, Martino; Kurniawan, Wakhid; Rekarti, Endi; Kurniawan, Anton; Chuaynugul , Sompong (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2023)
This study is intended to help craftsmen as well as small micro-scale shoe producers to comprehend the external and internal conditions of their business, the strengths and weaknesses of the business unit, and opportunities and threats to the business unit. As part of that, it provides alternative strategy options to be recommended to the small company holders to assist them to overcome their problems. Thus, the businesses owned by MSMEs who are members of joint business groups in Sukaresmi Village, Tamansari District, Bogor can survive and maintain their sustainability amid increasingly fierce-forcing competition among shoe entrepreneurs. The data analysis method used to evaluate the appropriate competitive strategy are using three stages coaxial of analysis. First, using the IFE and EFE matrix; Second, using IE and SWOT analysis and third using QPSM analysis. To sum up, it is concluded that the KUBE- Junashoe joint business group, at Sukasari Village, Tamansari District, Bogor, should be able to upscale their firm, by increasing promotion and product quality and upskilling the employee. Additionally, develop product and sales innovation, implement branding strategies and other strategies increasing support sales profitability.